Development, evaluation and validation of a financial stress scale for traders working in financial market - Saoji, Ajeet; Saoji, Prachi; Mitra, Arun; Hajare, Shilpa Trilok (Indian Journal of Community Health, 2019)
Background: Stress due to financial aspects in life is increasingly common in today's world. It can lead to psychological consequences such as anxiety, depression and can also lead to other non-communicable disorders. Previous scales to measure stress; which are generalized and does not necessarily include the financial aspects of stress. Aims & Objectives The purpose of this research is to develop a valid and reliable instrument that can be used to assess stress among day-traders of stock market. Material & Methods: In a cross-sectional survey a questionnaire was prepared based on in-depth interviews with day-traders of stock market. Construct validity, test-retest reliability and inter-rater reliability were carried out. Cronbach's alpha ( ) was 0.85 for the 11 short-listed items, with item-total correlations of 0.2–0.8. Multidimensional scaling determined 2 dimensions – work related and non-work related. Result: Results from this first study among day-traders in India indicate that traders are not immune to financial stress, with (78.9%) reporting high work related stress, (7.7%) reporting moderate work related and (13.4%) reporting low work related stress. Conclusion: this study identified a set of psychosocial stressors among day-traders and a stress scale (The Financial Stress Scale) was developed in the South Asian context.